Precision 3D modelling based on photographic data - Martínez Rodríguez, Santiago (Servizo de Publicacións e Intercambio Científico da USC, 2014)
Close-range photogrammetry is nowadays an achievable tool of measurement within the reach of any user that allows the representation in three dimensions of any object. This is achieved through the use of a camera or camera mobile phone and three-dimensional modelling 123D Catch free software. With the realization of the practical cases raised in didactic and simple way, it can be learned how to use the technology at our disposal to get 3D models of objects, scale them, measure them, and determine their coordinates. This manual may be of special interest to the participants of the International Championship in 3D Precision Modelling on Mobile Phones, www.d3mobile.es, because it helps to tackle and delves into the exercises and tests proposed in the championship, providing the opportunity to investigate what metric quality can be achieved on a 3D model and to improve the quality of the obtained models.